2023
DOI: 10.2337/db23-0030
|View full text |Cite
|
Sign up to set email alerts
|

Protective Renalase Deficiency in β-Cells Shapes Immune Metabolism and Function in Autoimmune Diabetes

Abstract: Type 1 diabetes (T1D) is caused by the immune-mediated loss of pancreatic beta cells that produce insulin. The latest advances in stem cell (SC)-beta cell differentiation methods have made a cell replacement therapy for T1D feasible. However, recurring autoimmunity would rapidly destroy transplanted SC-beta cells. A promising strategy to overcome immune rejection is to genetically engineer SC-beta cells. We previously identified Renalase (Rnls) as a novel target for beta cell protection. Here we show that Rnls… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(36 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…NK cells also upregulate gene expression of immune-regulatory Tgfβ1 when infiltrated in Rnls mut beta cell grafts (Supplemental Data Figure 1A and B). Interestingly, the frequency of NK cells in Rnls mut beta cell grafts was not only reduced in late stages 10 , but also at earlier time points preceding the detection of graft weight difference between control and Rnls mut (Supplemental Data Figure 1D and E; see Supplemental Data Figure 2 for gating strategy). Of note, the ILC1 frequency was not changed between the grafts and only represent a vast minority of infiltrating immune cells (≤ 1%) compared to NK cells (up to 14%) indicating that ILC1 likely does not play a major role in mediating the protective immune-regulation caused by Rnls mut beta cells 10 .…”
Section: Protective Immune-regulation By Rnls Mut Beta Cells Requires...mentioning
confidence: 99%
See 4 more Smart Citations
“…NK cells also upregulate gene expression of immune-regulatory Tgfβ1 when infiltrated in Rnls mut beta cell grafts (Supplemental Data Figure 1A and B). Interestingly, the frequency of NK cells in Rnls mut beta cell grafts was not only reduced in late stages 10 , but also at earlier time points preceding the detection of graft weight difference between control and Rnls mut (Supplemental Data Figure 1D and E; see Supplemental Data Figure 2 for gating strategy). Of note, the ILC1 frequency was not changed between the grafts and only represent a vast minority of infiltrating immune cells (≤ 1%) compared to NK cells (up to 14%) indicating that ILC1 likely does not play a major role in mediating the protective immune-regulation caused by Rnls mut beta cells 10 .…”
Section: Protective Immune-regulation By Rnls Mut Beta Cells Requires...mentioning
confidence: 99%
“…In addition to elevated numbers of CD4 + T cells and tolerogenic PD-L1 + APC, beta cell grafts deficient for Rnls showed markedly reduced frequency of NK cells. Because we previously demonstrated that PD-L1 blockade abrogates the advantage of Rnls mut beta cells to survive autoimmunity, and NK cells are known to modulate APC maturation and activation, we now investigated the role of NK cells in protection of Rnls mut beta cells in more detail 10 . The gene expression profile of both, graft-infiltrating NK cells and closely related type 1 innate lymphoid cells (ILC1), demonstrated markedly increased expression of genes involved in pathways of cellular activation and inflammation (interferon responses, allograft rejection, etc.)…”
Section: Protective Immune-regulation By Rnls Mut Beta Cells Requires...mentioning
confidence: 99%
See 3 more Smart Citations